Linear Bi-level Programming Problems - A Review - Wen, Ue-Pyng; Hsu, Shuh-Tzy (The Journal of the Operational Research Society, 1991)
Multi-level programming is characterized as mathematical programming to solve decentralized planning problems. The decision variables are partitioned among ordered levels. A decision-maker at one level of the hierarchy may have his own objective function and decision space, but may be influenced by other levels. During the last 10 years, a special case of the multi-level programming problem, the linear bi-level programming (BLP) problem, has been studied with increasing interest in the area of mathematical programming problems. This paper attempts to review the literature on the linear BLP problems. It presents the basic models and the characterizations of the problem, the areas for application, the existing solution approaches, and the related models and areas for further research.